Android for the beaglebone black : design and implement android apps that interface with your own custom hardware circuits and the beaglebone black /: design and implement android apps that interface with your own custom hardware circuits and the beaglebone black. (2015) - Henderson, Andrew; Prakash, Aravind
No abstract available